The Influence of Work Environment and Work Motivation on Employee Performance through Job Satisfaction as a Mediation Variable - Lilo, Angela Nathasia Grace; Ardiansari, Anindya (LifeSciFi, 2025)
This study aims to analyze the influence of work environment and work motivation on employee performance with job satisfaction as a mediating variable. A quantitative approach was used by a survey method of 158 employees of PT Cipta Panel Buana, a manufacturing company in Indonesia. Data was collected through a questionnaire based on the Likert scale and analyzed using Partial Least Square (PLS). The results of the study show that the work environment and work motivation have a significant effect on employee performance, both directly and indirectly through job satisfaction. Job satisfaction proved to be a powerful mediator in this relationship, with a 62.8% contribution to performance variability. These findings support the importance of creating a conducive work environment and an effective motivation system to improve employee satisfaction and performance. This research makes theoretical and practical contributions in the field of human resource management, especially in the context of the manufacturing industry